The Phenomenon of E-Cigarette Use Among the Young Generation in Banda Aceh, Indonesia - Syelvita, Cut Yayang; Fadhlullah, Fadhlullah; Abdullah, Asnawi; Zahara, Meutia; Adamy, Aulina (Jurnal Ners, 2025)
The increasing use of electronic cigarettes (e-cigarettes) among young adults in Indonesia has emerged as a growing public health concern. This qualitative study investigates the phenomenon of e-cigarette use among young people aged 18–25 in Banda Aceh by exploring the underlying motivations, knowledge levels, perceptions of health risks, and the influence of social and environmental factors. Data were collected through in-depth interviews with informants who actively use e-cigarettes. Thematic analysis revealed four major interrelated themes: reasons for use, knowledge about e-cigarettes, perceived health effects, and social support and accessibility. The findings show that many users are motivated by curiosity, a desire to follow modern trends, or as an attempt to switch from conventional cigarettes due to the perceived lower health risks. However, participants demonstrated varying levels of knowledge—while some were aware of basic components like nicotine and flavoring agents, few had an accurate understanding of long-term health impacts. Most informants believed that e-cigarettes are a “safer” alternative, despite acknowledging that their safety is not guaranteed. Social factors, such as peer influence and the presence of family members who also smoke, play a major role in normalizing the behavior. Additionally, easy access to vape products, aggressive marketing through social media, and appealing flavors further contribute to the habit’s popularity among youth. This study underscores that e-cigarette use in Banda Aceh is a socially and culturally embedded behavior, calling for comprehensive public education, regulatory enforcement, and targeted interventions to mitigate future health risks.